Analisis Peran Media Cetak Photobook Dalam Mempromosikan Brand Identity Dan Produk Untuk Bengkelmotor Custom Di Kota Tangerang - Andre Siauw (VisArt: Jurnal Seni Rupa dan Design, 2024)
Abstract: The rapid development of automotive trends in Indonesia, especially in the field of custom motorbikes, is reflected in the increasing number of custom workshops. However, most still often face challenges in attracting the attention of potential customers. The main problem is the lack of available information, which hinders the introduction of workshops and raises doubts among consumers in Tangerang City. The public's high interest in vehicle modifications underlines the important role of print media such as catalogs or photobooks in introducing brand identity and various products from custom workshops. The main objective of this design is to make this print media, in the form of a custom workshop brand identity, able to be presented effectively to the public, while the variety of products offered can be explained in detail, facilitating better understanding for potential consumers. The research method used is a qualitative method which places greater emphasis on data quality. The expected achievements and targets will be able to contribute to the progress of costume workshops in the city of Tangerang.